Characterization Techniques Coupled with Mathematical Tools for Deepening Asphaltene Structure - Barbara Apicella; Anna Ciajolo; Andrea Carpentieri; Ciprian Popa; Carmela Russo (Fuels, 2022)
Asphaltenes are the heavy fraction of fossil fuels, whose characterization remains a very difficult and challenging issue due to the still-persisting uncertainties about their structure and/or composition and molecular weight. Asphaltene components are highly condensed aromatic molecules having some heteroatoms and aliphatic functionalities. Their molecular weights distribution spans in a wide range, from hundreds to millions of mass units, depending on the diagnostic used, which is mainly due to the occurrence of self-aggregation. In the present work, mass spectrometry along with size exclusion chromatography and X-ray diffraction analysis have been applied to asphaltenes for giving some further insights into their molecular weight distribution and structural characteristics. Relatively small polycyclic aromatic hydrocarbons (PAHs) with a significant degree of aliphaticity were individuated by applying fast Fourier transform (FFT) and double bond equivalent (DBE) number analysis to the mass spectra. X-ray diffraction (XRD) confirmed some aliphaticity, showing peaks specific of aliphatic functionalities. Size exclusion chromatography indicated higher molecular weight, probably due to the aliphatic substituents. Mass spectrometry at high laser power enabled observing a downward shift of molecular masses corresponding to the loss of about 10 carbon atoms, suggesting the occurrence of aryl-linked core structures assumed to feature asphaltenes along with island and archipelago structures.